Importance of timely management of patients in reducing fatality rate of coronavirus disease 2019 - Yuzhu Peng; Biyun Xu; Beicheng Sun; Guangshu Han; Yi-Hua Zhou (Elsevier, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) characterized with pneumonia, firstly occurred in Wuhan city, China, in December 2019 has so far spread in over 200 countries and territories in the world. One of the important goals in facing outbreaks of COVID-19 is to reduce the case fatality rate. We reported here that the fatality rate of COVID-19 in other provinces of mainland China was 0.82% (121/14,708), significantly lower than 6.62% (4512/68,128) in Hubei province (p < 0.0001). The main reason for the lower fatality rate was likely due to the timely management of the patients in other provinces, highlighting the importance of timely management of patients in reducing the fatality rate of COVID-19.